PENGARUH JENIS MINYAK NABATI TERHADAP KARAKTERISTIK FISIK SEDIAAN BALSAM STICK EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) - Fitria Nugrahaeni; Ari Widayanti; Gede Andika Primatama (Universitas Wahid Hasyim Semarang, 2022)
Cherry leaves extract contain flavonoids which function as anti-inflammatory can be formed into stick balm preparations. The Stick balm is a preparation in the form of a stick consisting of a mixture of oil, wax and fat with a composition such that it can produce hardness and melting pont of as needed. The different properties of fatty acids in each type of oil can affect the physical properties of the balsam stick preparation in the form of melting point and hardness. This study aimed to determine the effect of adding olive oil, virgin coconut oil, castor oil, jojoba oil on the physical properties of the stick balm of Muntingia calabura L leaf extract. Physical characteristic of stick balm includes organolepti, homogeneity, melting point, hardness, and pH test. The results showed that all formulas met the physical characteristics of stick balms but each formula had differences in melting point, hardness, adhesion, and pH. The formula with the addition of olive oil showed the highest melting points and hardness at 55.3ºC and 8.16 mm. The results of statistical data was sig <0.05. This means that there are differences in melting point and hardness in each equation. Based on obeservations, it was concluded that the addition of vegetable oil to the balsam stick formulation affected the melting point and hardness.